Investment Climate in Africa - Bridgman, David; Adamali, Aref (World Bank, Washington, DC, 2015)
The World Bank Group has been working on investment climate reform in Sub-Saharan Africa for nearly a decade, a period characterized by dramatic economic growth on the continent. Establishing links between such reform interventions and economic growth, however, is a complex problem. Although this note finds some connection between investment climate reform and economic growth, establishing more concrete evidence of causation will require greater focus at the country level, as well as on small and medium enterprises. This is where investment climate interventions generate change.